2010
DOI: 10.1260/2040-2295.1.3.435
|View full text |Cite
|
Sign up to set email alerts
|

Graph Analysis and Visualization for Brain Function Characterization Using EEG Data

Abstract: Over the past few years, there has been an increased interest in studying the underlying neural mechanism of cognitive brain activity as well as in diagnosing certain pathologies. Noninvasive imaging modalities such as functional magnetic resonance imaging (fMRI), positron emission tomography (PET), and dynamic signal acquisition techniques such as quantitative electroencephalography (EEG) have been vastly used to estimate cortical connectivity and identify functional interdependencies among synchronized brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 95 publications
1
5
0
Order By: Relevance
“…All experiments showed that binary clustering coefficient and weighted average neighbourhood degree in effective networks enables us to differentiate alcoholics from normal subjects. This result is similar to results published in another research (Sakkalis et al 2010). Here, each node of weighted node betweenness centrality was compared between normal subjects and alcoholics, showing significant difference.…”
Section: Discussionsupporting
confidence: 91%
“…All experiments showed that binary clustering coefficient and weighted average neighbourhood degree in effective networks enables us to differentiate alcoholics from normal subjects. This result is similar to results published in another research (Sakkalis et al 2010). Here, each node of weighted node betweenness centrality was compared between normal subjects and alcoholics, showing significant difference.…”
Section: Discussionsupporting
confidence: 91%
“…where k u and k v are the degrees of the end vertices u and v, respectively, of edge {u,v} ∈ E. For directed unweighted graphs the above measure can still be used if we ignore the direction of edges [7]. The assortativity coefficient r lies in the range À1 r 1, where À1 indicates totally disassortative network while 1 indicates a totally assortative network.…”
Section: Average Vertex Degreementioning
confidence: 99%
“…The clustering coefficient for the whole graph is the average of C i for each node, C ¼ ∑ i ¼ 1 n C i /n, and is a measure of the tendency of graph nodes to form local clusters [7]. For unweighted graphs, the local CC associated with a node i having k i connections is defined as the ratio of the triangles that contain this node divided by the maximum possible number of such triangles k i (k i À 1)/2.…”
Section: Clustering Coefficientmentioning
confidence: 99%
See 1 more Smart Citation
“…However, more sophisticated interdependence techniques addressing not only linear but also nonlinear synchronization and causality are also available and applied in certain pathologies like Epilepsy [ 12 ]. Such measures can act complementary to graph theoretic indices that characterize brain networks as discussed in [ 19 ] and can be used as input to BrainNetVis.…”
Section: Introductionmentioning
confidence: 99%